Modelling distortion reduction on pre- and post-weld rolled gas metal arc welded plates - Cozzolino, Luis D.; Coules, Harry E.; Colegrove, Paul A.; Wen, S. W. (Cranfield University, 2011)
Residual stress generated during welding can cause distortion, especially when appliedon relatively thin plates. There are several standard and well documented techniquesto reduce distortion and residual stress after welding, however these techniques areoften costly and time consuming to implement on an industrial scale. In this paper wedemonstrate the pre- and post-weld rolling techniques for reducing weld distortion. Pre-Weld Rolling (PWR) can be applied before fabrication, potentially by the steelmanufacturer. An experimental investigation indicated that there was an average 38%reduction of distortion with this technique. Finite element analysis (FEA) was used todetermine the stress distribution to understand the phenomenon.